2013
DOI: 10.1073/pnas.1220301110
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structure of water at elevated pressures and temperatures

Abstract: We report on the microscopic structure of water at sub-and supercritical conditions studied using X-ray Raman spectroscopy, ab initio molecular dynamics simulations, and density functional theory. Systematic changes in the X-ray Raman spectra with increasing pressure and temperature are observed. Throughout the studied thermodynamic range, the experimental spectra can be interpreted with a structural model obtained from the molecular dynamics simulations. A spatial statistical analysis using Ripley's K-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 74 publications
1
99
0
Order By: Relevance
“…46,56−66 Although the correlations are not straightforward, it has been shown that the pre-edge is sensitive to the number of hydrogen bonds. 46,[58][59][60]62,63,65 Especially the differences in the donating hydrogen bonds affect the pre-edge. 63 The intensity in the postedge area is related to tetrahedral ordering of the system.…”
Section: ■ Methodsmentioning
confidence: 99%
“…46,56−66 Although the correlations are not straightforward, it has been shown that the pre-edge is sensitive to the number of hydrogen bonds. 46,[58][59][60]62,63,65 Especially the differences in the donating hydrogen bonds affect the pre-edge. 63 The intensity in the postedge area is related to tetrahedral ordering of the system.…”
Section: ■ Methodsmentioning
confidence: 99%
“…We assign the components C2 and C3 at ~3450 cm -1 and ~3580 cm -1 to ν 1 and ν 3 of H 2 O monomers (e.g., Walrafen, 1962). The component C1 at ~3280 cm -1 is assigned to O-H stretching vibrations of strongly hydrogen-bonded, polymerised water species because the relative intensity of this component correlates with the dependence of polymerisation on pressure and temperature (e.g., Sahle et al, 2013) and decreases with addition of salt (e.g., Walrafen, 1962).…”
Section: Compression-enhanced Contact Ion Pairingmentioning
confidence: 99%
“…[26]. Experimental studies have provided insights for the structure of near-critical water [33,34]; however, there has been relatively little theoretical work on thermophysical properties of bulk water near the critical point.…”
Section: Introductionmentioning
confidence: 99%